Undesired effects of psychoactive substances consumed by students of physiotherapy - Kijowski, Stanisław (European Journal of Clinical and Experimental Medicine, 2013)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Increased mental and physical activity states are the reason to search and ingest cognitive functions aids by students, especially during upcoming finals and examination sessions. The aim of this study was to assess the scale of the use by students of cognitive aids. Evaluation was performed of: types of substances used by students, quantity of ingested psychoactive substances, effects of substances used, and outcome awareness level after ingestion of “psychoactive” substances. Study questionnaire involved 254 students of both genders, at the age of 19-25 from four academic institutes in the country. Based on the analysis results indicated that most common psychoactive substance used by the surveyed students are the energy drinks (21% of respondents), 19% of surveyed used vitamin supplements, 10% regularly drinks coffee, 8% used “plusssz active” substance, 5% of respondents indicated the intake of lecithin and carnitine. Study showed that the combination of ephedrine and energy drinks were used by 4% of respondents also 4% used creatine. Among the side effects of the psychoactive substances in the first place are vegetative disorders (33%), sleep disorders (19%), addiction (11%), metabolic disorders (8%), trouble concentrating (6%), slowed reflexes (6%), and asthenia (3%). Most psychoactive substances are applied during the finals and examination sessions (60%), during workout (28%), to remove the symptoms of fatigue (6%), remaining 6% of the respondents ingests psychoactive substances on a daily bases. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusions: 1. There were no differences in the use of psychoactive substances among men and women. 2. Most consumed psychoactive agent is energy drinks. 3. The main reason of use of psychoactive substances by students is the desire to improve concentration before the examination session.